Antimicrobial Resistance (AMR) Patterns in Community-Acquired Infections - Muhammad Zishan Akhtar Wali, Najam Azam, Saleha Afridi, Qamar Sajad, Maryam Nadeem, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: To determine the prevalence and antimicrobial resistance patterns of bacterial isolates obtained from patients with community-acquired infections presenting to Jinnah Hospital, Lahore. Methods: A cross-sectional study was carried out at the department of Medicine, Jinnah Hospital, Lahore, from June 2022 to May 2023. A total of 82 patients with clinically diagnosed community-acquired infections were enrolled. Clinical specimens were collected, cultured, and bacterial isolates were identified using standard microbiological techniques. Antimicrobial susceptibility was assessed by the Kirby-Bauer disk diffusion method in accordance with Clinical and Laboratory Standards Institute (CLSI) guidelines. Data were analyzed using SPSS version 26. Results: The most common infections were urinary tract (37.8%) and respiratory tract infections (28%). Escherichia coli (34.1%) was the predominant isolate, followed by Staphylococcus aureus (20.7%) and Klebsiella pneumoniae (18.3%). Resistance rates were highest against fluoroquinolones (76.8%), β-lactams (74.4%), and cephalosporins (69.5%), while carbapenems showed the highest sensitivity (75.6%). Multidrug resistance was observed in 34.1% of isolates, and MRSA was frequently detected among Gram-positive organisms. Conclusion: The study highlights a high prevalence of resistance among community-acquired infections, particularly to commonly prescribed antibiotics such as fluoroquinolones and cephalosporins. The emergence of carbapenem resistance and multidrug-resistant organisms underscores the urgent need for antimicrobial stewardship, rational prescribing, and community-level awareness programs. Keywords: Antimicrobial resistance, Community-acquired infections, Escherichia coli, Multidrug resistance.